Ответ: -11. 6,5.
Объяснение:
3) (6 3/8 - 2 3/4)*(-4)+7/18*9 = -11;
По действиям:
1) 6 3/8 - 2 3/4=6 3/8 - 2 6/8 = 4 (3-6)/8 = 3 (11-6)/8=3 5/8;
2) 3 5/8 * (-4) = -29/8*4 = -29/2;
3) 7/18*9=7/2;
4) -29/2 + 7/2 = -22/2 = -11;
---------------
4) 9 1/6 : (4 1/3-8)+24*3/8= 6.5
1) 4 1/3-8=-3 2/3;
2) 9 1/6 : (-3 2/3)= -55/6 : 11/3= -5/2=-2.5;
3) 24*3/8 = 9;
4) -2.5 + 9=6.5.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: -11. 6,5.
Объяснение:
3) (6 3/8 - 2 3/4)*(-4)+7/18*9 = -11;
По действиям:
1) 6 3/8 - 2 3/4=6 3/8 - 2 6/8 = 4 (3-6)/8 = 3 (11-6)/8=3 5/8;
2) 3 5/8 * (-4) = -29/8*4 = -29/2;
3) 7/18*9=7/2;
4) -29/2 + 7/2 = -22/2 = -11;
---------------
4) 9 1/6 : (4 1/3-8)+24*3/8= 6.5
1) 4 1/3-8=-3 2/3;
2) 9 1/6 : (-3 2/3)= -55/6 : 11/3= -5/2=-2.5;
3) 24*3/8 = 9;
4) -2.5 + 9=6.5.